2000
DOI: 10.1055/s-2000-9467
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Gait Variable Differences between Basketball, Swimming and Soccer Players

Abstract: The gait variables of 10 swimmers, 10 basketball players, and 16 soccer players were compared. They were all male and right-handed. There was no statistical difference between the three groups in age, weight and height. Spatial and temporal gait variables were measured with the Bessou gait analyzer. In the swimmers group, the gait variables of the right side were not statistically different from those of the left side. The right propulsion double support duration, right cycle duration, and right late swing pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
7
16
0
Order By: Relevance
“…The risks of bone, joint and muscle overload-related trauma and pathologies have been reported to be high in rugby players [3,[15][16][17][18]. Our findings of foot support anomalies in rugby players with respect to controls gives further support to this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The risks of bone, joint and muscle overload-related trauma and pathologies have been reported to be high in rugby players [3,[15][16][17][18]. Our findings of foot support anomalies in rugby players with respect to controls gives further support to this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…Leroy et al [3] have shown evidence of variations of foot support in subjects who practice sports intensely. Such differences are related to the performance model, in that there are specific loads and postural adaptations for each sport discipline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only bilateral asymmetries observed were for the professional level athletes on isokinetic and functional evaluations when previous knee injury was taken into account, such that the injured limb did not perform as well as the uninjured limb. These are interesting findings, as other researchers state that since basketball is somewhat a unilateral sport, most players have a preferential lay-up that is dependent on handedness (Leroy et al, 2000).…”
Section: Injury Risksupporting
confidence: 54%
“…Gait variables have been studied in basketball and soccer players, as well as swimmers to determine if playing a specific sport has an influence on gait pattern, thus leading to an asymmetric gait (Leroy, Polin, Tourny-Chollet, & Weber, 2000).…”
Section: Neural/controlmentioning
confidence: 99%